2014
DOI: 10.1017/s0007114514001536
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and saponins extracted from black bean (Phaseolus vulgarisL.) seed coats modulate lipid metabolism and biliary cholesterol secretion in C57BL/6 mice

Abstract: Black bean (Phaseolus vulgaris L.) seed coats are a rich source of natural compounds with potential beneficial effects on human health. Beans exert hypolipidaemic activity; however, this effect has not been attributed to any particular component, and the underlying mechanisms of action and protein targets remain unknown. The aim of the present study was to identify and quantify primary saponins and flavonoids extracted from black bean seed coats, and to study their effects on lipid metabolism in primary rat he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…The pharmacological functions of flavonoid compounds include multiple-treatment effects against various systematic diseases, including cardiovascular, neurological, immunological, endocrinology, and respiratory symptoms (Chavez-Santoscoy et al, 2014;Daddam et al, 2014;Sankari et al, 2014). These studies also revealed promising treatment effects of flavonoid compounds against liver damage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The pharmacological functions of flavonoid compounds include multiple-treatment effects against various systematic diseases, including cardiovascular, neurological, immunological, endocrinology, and respiratory symptoms (Chavez-Santoscoy et al, 2014;Daddam et al, 2014;Sankari et al, 2014). These studies also revealed promising treatment effects of flavonoid compounds against liver damage.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, promising results in the treatment of liver fibrosis have been reported using Chinese medicine (Li et al, 2014b;Zhang et al, 2014a), which often contain flavonoid compounds (Fu et al, 2014). Current studies have revealed multiple pharmacological roles of flavonoid compounds, including the treatment of tumors, cardiovascular disease, and diabetes (Chavez-Santoscoy et al, 2014;Daddam et al, 2014;Sankari et al, 2014). To further study the effect of flavonoid compounds extracted from Iris plants on liver fibrosis, we developed liver fibrosis model rats using carbon tetrachloride (CCl 4 ) and measured indices of liver function, liver fibrosis, and tissue pathological changes to evaluate their effects on CCl 4 -induced rat liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…They found that after QUE injection the level of TBAs in rats bile was enhanced. Recently another group of resear chers reported that QUE, isolated from black beans, activated TBAs secretion in mice liver [18].…”
Section: Resultsmentioning
confidence: 99%
“…18 h of food deprivation. Every rat was anesthetized with thiopentalum natrium (Ukraine, OAO "Kyivmedpreparat", 6 mg/100 g rat b.w.).…”
Section: Corvitin Is a Soluble Form Of Quercetin (Que) And Its Effectmentioning
confidence: 99%
“…In addition, beans can provide phenolic compounds with antioxidant activity and phytosterols. Phytosterols and phenolic compounds from the black bean seed coat can potentially reduce cholesterol levels via the gut microbiota [34], by inhibiting the micellar solubility of cholesterol and reducing the expression of lipogenic genes [35,36]. A link has been suggested between the consumption of foods rich in polyphenols and the reduction of the incidence of numerous chronic disorders; however, inside the human body, the chemical structure of most polyphenols is received as xenobiotic and, therefore, the bioavailability of these compounds is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%